Legally acceptable process for cosmetic products: A jurisprudencial analytical study - Muneer Ali Abdul Rab; Hoque M.; Fattah W.A.; Sahid M.M.; Gunardi S.B. (IAEME Publication, 2024)
Indexed by SCOPUS